KIDNEY TRANSPLANTATION AND DISTAL SPLENORENAL VENOUS ANASTOMOSIS IN THE TREATMENT OF DIABETIC NEPHROPATHY - T. A. Piminova; A. A. Salmayer; T. I. Shraer; A. M. Putincev; S. A. Syomina; N. K. Galcovsky; V. A. Lucenko (Вестник трансплантологии и искусственных органов)
A cadaveric kidney transplantation (KT) combined with distal venous splenorenal anastomosis is suggested as the surgical method for type 1 diabetes treatment (Shraer T.I.). This kind of operation was performed in 3 patients with the late stage of diabetic nephropathy (plasma creatinine 0,35–0,49 mmol/l). The results of our analysis showed positive influence of the above mentioned surgical treatment, reflect on the diabetes nephropathy, neuropathy and angiopathy.